Aplikasi Melati Air Dalam Menurunkan BOD dan COD Limbah Cair Kelapa Sawit - Gusmita, Mike; Fitrada, Wathri; Ervil, Riko (Riset Sinergi Indonesia, 2022)
Wastewater produced oil industry mustard t containing organic content of high BOD and COD. BOD and COD stating the amount of dissolved oxygen needed by microorganisms to decompose the material organic of a waste. Therefore, high levels of BOD and COD must be lowered in organic levels before being discharged into the water. One way that can be done using phytoremediation technology that is environmentally friendly. The purpose of this research to see the effectiveness of the water jasmine plant's ability to reduce levels of BOD and COD in palm oil industrial wastewater. This study used a batch system with variations in the number of plants used were 4, 12 and 16 individual plants and variations in contact time of 5 and 9 days. The initial testing of the waste obtained a BOD value of 4,236 mg / L, and a COD value of 5760 mg / l. After the phytoremediation test was carried out, the best decrease in BOD values was up to 96 mg / L and the greatest efficiency was obtained 97.73%. The decrease also occurred very well in COD, namely up to 342 mg / L with the greatest efficiency obtained by 93.88%. The decrease in the optimum levels of BOD and COD was found in variations in the number of plants 16 and on the 9th day. This proves that these plants are effective in eliminating liquid waste levels in the palm oil industry, especially BOD and COD